2015
DOI: 10.1007/s13277-015-4295-0
|View full text |Cite
|
Sign up to set email alerts
|

Association of promoter polymorphisms of Fas –FasL genes with development of Chronic Myeloid Leukemia

Abstract: Chronic myeloid leukemia (CML) is a monoclonal myeloproliferative disorder of hematopoietic stem cells (HSCs), characterized by reciprocal translocation, leading to the formation of BCR-ABL oncogene with constitutive tyrosine kinase (TK) activity. This oncogene is known to deregulate different downstream pathways which ultimately lead to cell proliferation, defective DNA repair, and inhibition of apoptosis. Fas (Fas cell surface death receptor) is a member of tumor necrosis factor (TNF) superfamily which inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 32 publications
2
14
0
Order By: Relevance
“…Polymorphisms in FAS gene may decrease the apoptotic potential of the receptor, and have been associated with several illnesses, including cancer and musculoskeletal degenerative disorders [100,101]. Furthermore, there are studies demonstrating the association of FAS polymorphisms with the persistence of HTLV infections and its clinical manifestations, such as Adult T-Cell Leukemia (ATL) and HTLV-1-associated myelopathy (HAM) [102,103,104].…”
Section: Extrinsic Pathwaymentioning
confidence: 99%
“…Polymorphisms in FAS gene may decrease the apoptotic potential of the receptor, and have been associated with several illnesses, including cancer and musculoskeletal degenerative disorders [100,101]. Furthermore, there are studies demonstrating the association of FAS polymorphisms with the persistence of HTLV infections and its clinical manifestations, such as Adult T-Cell Leukemia (ATL) and HTLV-1-associated myelopathy (HAM) [102,103,104].…”
Section: Extrinsic Pathwaymentioning
confidence: 99%
“…Similarly, research has shown that CD95-670 G>A and CD178 −844 T>C SNPs are associated with the progression of CML toward accelerated and blast phases. 21 Given that CD95/CD178 is involved in the apoptosis process, these genetic changes could influence blast cells ’ resistance to apoptosis by affecting the expression and alteration of intracellular mechanisms. Indeed, this finding suggests that CD95/CD178 SNPs as potential prognostic factors provide for different degrees of disease progression in CML patients and are important in defining high-risk groups.…”
Section: Discussion and Future Perspectivementioning
confidence: 99%
“…Although no association has been reported between CD95-1377 SNP and chronic myeloid leukemia (CML), research has shown that -670 GG and CD178 −844 TC SNPs are associated with increasing risk of CML and disease progression to accelerated and blast phases. 21 Unlike what observed in AML and CML, Tong et al . demonstrated that children carrying CD95 (-1377A, -670G) and CD178 (-844C) polymorphisms had reduced risk of acute lymphoblastic leukemia (ALL).…”
Section: Effect Of CD Markers’ Polymorphisms On the Clinical Outcome mentioning
confidence: 90%
“…However, the host genetic susceptibility factors favoring CML development have not been identified yet. Genetic variations such as functional single nucleotide polymorphisms (SNPs) in the apoptosis regulatory genes have been shown in the pathogenesis of malignant tumors and autoimmune diseases (Edathara et al, 2016).…”
Section: Impact Of Fas/fasl Gene Polymorphisms On Susceptibility Riskmentioning
confidence: 99%